Game theoretic models for a closed-loop supply chain with stochastic demand and backup supplier under dual channel recycling - Giri, Bibhas Chandra; Dey, Sushil (Decision Making: Applications in Management and Engineering, 2020)
In this paper, a dual-channel closed-loop supply chain is consi-dered for waste recycling. The manufacturer produces the finished product using recycled and recyclable waste materials as well as fresh raw materials. The recyclable wastes collected by the collector are supplied to the manufacturer directly or indirectly via a third party (recycler). Two different game models are considered for two different cases of recycling: recycling by the manufacturer and recycling by the recycler. If the collector fails to supply the required amount of waste materials, the backup supplier meets up the shortfall by supplying fresh raw materials. The customer demand is assumed to be stochastic. Optimal results for the two game models are obtained through numerical examples. It is seen that ex-ante pricing commitment i.e, fixed markup strategy is beneficial for the whole supply chain as well as the supply chain entities, compared to the decentralized policy. From the numerical study, it is also observed that when the recyclability degree of wastes increases, the expected total profit increases for the whole supply chain. A higher price sensitivity of customer demand leads to lower profit for the chain members.